Pendampingan Kegiatan Rapi Administrasi di UKM Pakis Malang - Muhammad Syafriel; Novy Karmelita Indrawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
It very important for business administration to e carried out in a structured and consistent manners in its execution. If it is not done well, it will become negative feedback in the course of the business and will reduce competitiveness. The activity of administraive tidiness is used for continuous improvement of the administrative system by adjusting the availale resouces, including human resources and technology. This community service aims to provide insights, knowledge, and skills in the implementation of administrative therapy activities through socialization, training and guidance on administrative writing, particularly in production and warehousing. The implementation leads to improved efficiency and effectiveness in working time, tidiness and ease of work. In addition, it makes coordination between employees and departements easier, while accountability is achieved.